Improving the Hybrid Ad hoc Network Routing Performance Using RMECR Algorithm and Lightweight protocol (International Journal of Engineering and Computer Science, 2017)
The work deals with the problem of energy-efficient reliable wireless communication in the presence of unreliable or loss wireless link layers in multi-hop wireless networks. RMER and RMECR are proposed for networks in which either hop-by-hop or end-to-end retransmissions ensure reliability. Simulation studies show that RMECR is able to find energy-efficient and reliable routes similar to RMER while also extending the operational lifetime of the network. This makes RMECR an elegant solution to increase energy efficiency, reliability and lifetime of wireless ad hoc networks. We conducted extensive simulations to study the power consumption, the end-to-end delay and the network throughput of our protocols compared with the existing protocols. In contrast to the conventional power-aware algorithms, the Maximum Residual Packet Capacity (MRPC) identifies the capacity of a node not just by its residual battery energy but also by the expected energy spent in reliably forwarding a packet over a specific link. In this paper we argue that such a formulation based solely on the energy spent in single transmission is misleading —the proper metric should include the total energy (including that expended for any retransmissions necessary) spent in reliably delivering the packet to its final destination. In focus of achieving secure communication and preserving user’s privacy in hybrid ad hoc wireless networks, to preserve user’s anonymity each node uses pseudonyms and one-time session key. In addition to secure the communication, this paper develops efficient pseudonym generation and trapdoor techniques require only lightweight hashing operations and a payment system.